Implementation Of Public Consultation In The Framework Of Land Procurement For Toll Road Construction In The Public Interest (Study Of Toll Road Development In The Kauman District, Tulungagung Regency) - Dwi Astutik, Senia; Sunardi, Sunardi (International Significance of Notary, 2025)
Abstract : This research examines the implementation of public consultations in the context of land acquisition for toll road construction in the Kauman District, Tulungagung Regency, using empirical juridical methods and statutory approaches. The aim of this research is to analyze the effectiveness and transparency of the public consultation process and its impact on the welfare of local communities. The research results show that the implementation of public consultations in Kauman District went smoothly and succeeded in achieving agreement from all residents regarding the construction of the toll road. The consultation process is carried out transparently and fairly, ensuring that no party is harmed. The consultation in Batangsaren Village was carried out in two stages, considering the expansion of affected land. This process aims to fulfill common interests and improve regional infrastructure by paying attention to the welfare of residents. For people who cannot attend public consultations, this research found that there are several solutions to ensure their participation remains represented. The community can be represented through a power of attorney, as well as the formation of a WhatsApp group as an additional medium to reach and involve those who cannot be physically present. Through these groups, important information is disseminated, discussions are held, and feedback from the community is gathered, ensuring broader and more inclusive participation in the decision-making process.